Pengintegrasian Sistem BLU-E Dan Aplikasi Ferizy Sebagai Mitigasi Kendaraan Over Dimension Over Load (ODOL) Di Pelabuhan Penyebrangan Merak - Ahmad Baehaki; Johannes Valentino Sinaga; Ghufrillah Arma Danti; Putri Ainiyyah Hafizha (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
This study proposes integration between the BLU-e (Electronic Test Pass Proof) system and the Ferizy application to mitigate Over Dimension Over Load (ODOL) vehicles at the Merak Crossing Port. ODOL can endanger the safety of passengers and drivers. The merger of the two systems aims to identify vehicles that violate the dimensions and permitted cargo and prevent them from entering ships at the port. This study explains the concept of ODOL, dimensional and payload limitations, and the importance of vehicle weighing. The proposed method involves inputting class and vehicle class data into the Ferizy app during ticket purchase, then cross-checking with BLU-e data and physical inspection by officers. ODOL vehicles will be detected and prohibited from using crossing services while being warned. This integration is expected to improve security and compliance with ODOL regulations at the Merak Crossing Port.